Imaging of Tropical Chronic Pancreatitis-A Unique Clinico-Radiological Entity - Chinmay Bhimaji Kulkarni; Resmi Sekhar; Srikanth Moorthy; Sreekumar Karumathil Pullara; Nirmal Kumar Prabhu; Ramiah Rajesh Kannan (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Tropical chronic pancreatitis (TCP) is a unique juvenile nonalcoholic form of chronic pancreatitis prevalent in tropical developing countries. TCP is characterized by the younger age of onset, rapid progression, higher prevalence of diabetes and pancreatic calculi, and greater propensity to develop pancreatic malignancy. Identifying the distinct imaging features is critical for the diagnosis of TCP. Awareness of this condition will not only enable the radiologist to recognize it early but also help in better management. In this article, we review the etiopathogenesis, distinct imaging features, and complications of TCP.